2017
DOI: 10.1111/1467-8500.12251
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding Theoretical Stagnation: A Systematic Review and Framework for Measuring Public Value

Abstract: Public value theory has become a hot topic in public administration research, but its proponents have long recognised difficulties in empirically testing the theory's central propositions. There has been a lack of clarity about how to measure the extent to which organisations are generating public value, which has rendered researchers unable to quantitatively study the causes, consequences and correlates of public value. The current study systematically reviews the growing literature on public value measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0
17

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(87 citation statements)
references
References 45 publications
1
69
0
17
Order By: Relevance
“…Spano (2014) adopts a similar approach investigating how managerial control systems can be used to understand if an organization has been able to achieve the planned outcomes and how this translated into the creation of PV. Moreover, studies have also called for further theoretical and empirical contributions on PV measurement (Faulkner & Kaufman, 2018;Hartley et al, 2017). In order to answer the third research question, we now focus on papers adopting an accounting perspective.…”
Section: Figure 8 Selected Papers Distribution By Public Value Core mentioning
confidence: 99%
“…Spano (2014) adopts a similar approach investigating how managerial control systems can be used to understand if an organization has been able to achieve the planned outcomes and how this translated into the creation of PV. Moreover, studies have also called for further theoretical and empirical contributions on PV measurement (Faulkner & Kaufman, 2018;Hartley et al, 2017). In order to answer the third research question, we now focus on papers adopting an accounting perspective.…”
Section: Figure 8 Selected Papers Distribution By Public Value Core mentioning
confidence: 99%
“…When AGT achieves scalability, we may continue our investigation with a quantitative data collection (such as a survey). One of the opportunities is to measure the public value among citizens, for instance, concerning the trust, legitimacy, service delivery quality, and efficiency of the blockchain application, as proposed by Faulkner and Kaufman (2018). The second-order effects are a hot topic around blockchain technology and sustainability.…”
Section: Resultsmentioning
confidence: 99%
“…A further and recent study by Faulkner and Kaufman [164] highlighted the different dimensions of Public Value measurement through an accurate and systematic analysis of the literature. Through a qualitative synthesis of the topics analyzed in literature, the authors have identified four dimensions of Public Value measurement that can be adapted to any context.…”
Section: Public Value As a Tool For Conceptualizing Performancementioning
confidence: 99%